(untitled) (Nexo Revista Científica, 2022)
There are many ways to send and receive an electronic message, but SMS is more popular and nowadays used for one time password (OTP) as a part of authentication in many web applications, internet of things (IoT) access, password reset, mobile banking (M-banking), etc. Therefore, we must know how the protocol works and about its security. This protocol is designed to manage federatively (i.e., the mobile network is managing partially by many independent operators and it doesn’t need to have a central operator for the whole network. Also, many independent centrally managed networks can connect together to make a bigger network). We reviewed SMS protocol and its network structure, message structure, network entities, entities’ connection, and some security-related issues. Finally, this protocol is evaluated if it can provide Identification, Authentication, Integrity, Nonrepudiation, Confidentiality, and Availability.